Issues in peace and conflict studies : selections from CQ researcher (SAGE, 2011)
Do nation-states have a "Responsibility to Protect"? Can countries heal after atrocities? Who should clean up after conflicts end? These questions and many more are at the heart of peace and conflict studies. This collection aims to promote in-depth discussion, facilitate further research and help readers formulate their own positions on crucial issues. It is intended to be a supplement for courses in peace and conflict studies that are offered in departments of psychology, sociology, anthropology, political science, and across all social science disciplines.